2022
DOI: 10.3390/en15165977
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Combined Heat and Power Systems by Meta-Heuristic Algorithms: An Overview

Abstract: Combined heat and power (CHP) plants are known as efficient technologies to reduce environmental emissions, balance energy costs, and increase total energy efficiency. To obtain a more efficient system, various optimization methods have been employed, based on numerical, experimental, parametric, and algorithmic optimization routes. Due to the significance of algorithmic optimization, as a systematic method for optimizing energy systems, this novel review paper is focused on the meta-heuristic optimization alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 191 publications
(207 reference statements)
0
7
0
Order By: Relevance
“…Moreover, Alsagri and Alrobaian [34] have presented a complete and updated overview of meta-heuristic optimization algorithms used in CHP systems, including the CHPED and CHPEED problems, in two categories of single objective and multi-objective algorithms. They divided the suggested algorithms in single objective for CHP optimization into evolutionary algorithms (EAs) (including GAs, differential evolution (DE) algorithm, hyper-spherical search (HSS), artificial immune system (AIS), and the stochastic fractal search (SFS) algorithms), swarm intelligence-based (SI-based) algorithms (including different variants of PSO, whale optimization algorithm (WOA), cuckoo search algorithm (CSA), group search optimization (GSO), FA, bee colony optimization (BCO), ant colony search algorithm (ACSA), squirrel search algorithm (SSA), and grey wolf optimization (GWO)), human-based algorithms (including harmony search (HS), teaching learning-based optimization (TLBO), exchange market algorithm (EMA), and social cognitive optimization (SCO)), physics-based algorithms (including gravitational search algorithm (GSA), charged system search algorithm (CSSA), and heat transfer search algorithm (HTS)), and hybrid meta-heuristic methods (including combining the meta-heuristics methods such as combinatorial time-varying acceleration coefficients-gravitational search algorithm-particle swarm optimization (TVAC-GSA-PSO), combining the bat algorithm (BA) and artificial bee colony (ABC) algorithm based on the chaotic-based self-adaptive (CbSA) (CbSA-BAABC), combining the meta-heuristics and the machine learning programming, and combining the meta-heuristics and the mathematical programming methods).…”
Section: A Brief Review Of Relevant Previous Research Workmentioning
confidence: 99%
“…Moreover, Alsagri and Alrobaian [34] have presented a complete and updated overview of meta-heuristic optimization algorithms used in CHP systems, including the CHPED and CHPEED problems, in two categories of single objective and multi-objective algorithms. They divided the suggested algorithms in single objective for CHP optimization into evolutionary algorithms (EAs) (including GAs, differential evolution (DE) algorithm, hyper-spherical search (HSS), artificial immune system (AIS), and the stochastic fractal search (SFS) algorithms), swarm intelligence-based (SI-based) algorithms (including different variants of PSO, whale optimization algorithm (WOA), cuckoo search algorithm (CSA), group search optimization (GSO), FA, bee colony optimization (BCO), ant colony search algorithm (ACSA), squirrel search algorithm (SSA), and grey wolf optimization (GWO)), human-based algorithms (including harmony search (HS), teaching learning-based optimization (TLBO), exchange market algorithm (EMA), and social cognitive optimization (SCO)), physics-based algorithms (including gravitational search algorithm (GSA), charged system search algorithm (CSSA), and heat transfer search algorithm (HTS)), and hybrid meta-heuristic methods (including combining the meta-heuristics methods such as combinatorial time-varying acceleration coefficients-gravitational search algorithm-particle swarm optimization (TVAC-GSA-PSO), combining the bat algorithm (BA) and artificial bee colony (ABC) algorithm based on the chaotic-based self-adaptive (CbSA) (CbSA-BAABC), combining the meta-heuristics and the machine learning programming, and combining the meta-heuristics and the mathematical programming methods).…”
Section: A Brief Review Of Relevant Previous Research Workmentioning
confidence: 99%
“…Others limit their scope to particular optimization strategies or theoretical frameworks, with each addressing only a fragment of the broader EDP landscape [11]. Additionally, certain reviews target specific types of power systems [12,13]. In contrast, the present research provides a comprehensive examination of the EDP, thus tracing its evolution from traditional to modern power systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [29], demonstrated that optimising design strategies in cogeneration reduces the cost of CO2. [30], optimised a CHP by utilising low pressure steam and the waste heat of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [29], demonstrated that optimising design strategies in cogeneration reduces the cost of CO 2 [30], optimised a CHP by utilising low pressure steam and the waste heat of the plant. [31], continued with the previous work to demonstrate how CHP configurations can be utilised to reduce the cost of production not only by using electricity and steam, but also CO 2 for enhanced oil recovery (EOR).…”
Section: Introductionmentioning
confidence: 99%